Search for quark-lepton compositeness and a heavy W' Boson using the enu channel in p p macro collisions at square root of [s] = 1.8 TeV. - Affolder, T; Akimoto, H; Akopian, A; Albrow, MG; Amaral, P; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; Asakawa, T; et al. (2001)
We present searches for quark-lepton compositeness and a heavy W' boson at high electron-neutrino transverse mass. We use approximately 110 pb(-1) of data collected in p p macro collisions at square root of [s] = 1.8 TeV by the CDF Collaboration during 1992-1995. The data are consistent with standard model expectations. Limits are set on the quark-lepton compositeness scale Lambda, the ratio of partial cross sections sigma(W'-->enu)/sigma(W-->enu), and the mass of a W' boson with standard model couplings. We exclude Lambda<2.81 TeV and a W' boson with mass below 754 GeV/c(2) at the 95% confidence level. Combining with our previously published limit obtained using the muon channel, we exclude a W' boson with mass below 786 GeV/c(2) at the 95% confidence level.